DIALOGICAL COMMUNICATION OF CENTRAL ADMINISTRATION IN TURKISH PUBLIC ADMINISTRATION: EXAMPLE OF MINISTRY WEBSITES - Tokgöz, Emircan; Tanyıldızı, Nural İmik (Ege University, 2022)
Dialogue approach of public relations has been discussed theoretically until the 2000s. Internet technologies, which have become widespread since these years, brought the applicability of dialogue in public relations to the agenda. The first comprehensive study suggesting that the dialogue, which is specific to interpersonal communication, can be realized with these new communication technologies was made by Kent and Taylor (1998). In the study, principles have been put forward on the use of websites that have the potential to adapt dialogue to the public relations activities of organizations. These principles are; dialogic loop, usefulness of information, user-friendliness of the interface, keeping visitors on the site and ensuring revisit. This study was carried out within the framework of dialogic principles that propose a web design suitable for dialogue. In the study, the websites of the ministries, which are among the Turkish public administration central government institutions, were analyzed on the basis of dialogic principles. With these analyses, it has been tried to reveal the dialogic public relations of the central government. For this purpose, the websites of all 16 ministries were examined during the study period. Content analysis method was used in the study. The findings obtained as a result of the analysis show that the websites are insufficient in the categories of ease of use and revisit, but successful in the principles of usefulness of information and keeping visitors on the site. Within the framework of the dialogic loop principle, which is emphasized in this study, it has been seen that the websites are quite inadequate.

Halkla ilişkilerin diyalog yaklaşımı, 2000’li yıllara kadar teorik olarak tartışılmıştır. Bu yıllardan itibaren yaygınlaşan internet teknolojileri, halkla ilişkilerde diyaloğun uygulanabilirliğini gündeme taşımıştır. Kişilerarası iletişime özgü olan diyaloğun, bu yeni iletişim teknolojileri ile hayata geçirilebileceğini öneren ilk kapsamlı çalışma Kent ve Taylor (1998) tarafından yapılmıştır. Çalışmada, kuruluşların halkla ilişkiler faaliyetlerine diyaloğu adapte edebilecek potansiyele sahip olan web sitelerinin kullanımı konusunda ilkeler ortaya konulmuştur. Bu ilkeler; diyalojik döngü, bilginin kullanışlılığı, arayüz kullanım kolaylığı, ziyaretçileri sitede tutma ve yeniden ziyareti sağlama şeklinde sıralanmaktadır. Bu çalışma, diyaloğa uygun bir web tasarımı öneren Kent ve Taylor’un diyalojik ilkeleri çerçevesinde yapılmıştır. Çalışmada, Türk kamu yönetimi merkezi yönetim kurumlarından olan bakanlıkların web siteleri diyalojik ilkeler temelinde analiz edilmiştir. Bu analizlerle, merkezi yönetimin diyalojik halkla ilişkileri ortaya konmaya çalışılmıştır. Bu amaçla, çalışma döneminde sayıları 16 olan bakanlıkların tamamının web siteleri incelenmiştir. Çalışmada içerik analizi yöntemi kullanılmıştır. Analiz sonucunda elde edilen bulgular, web sitelerinin, arayüz kullanım kolaylığı ve yeniden ziyareti sağlama kategorilerinde yetersiz, bilginin kullanışlılığı ve ziyaretçileri sitede tutma ilkelerinde başarılı olduğunu göstermektedir. Bu çalışmada önemle vurgulanan diyalojik döngü ilkesi çerçevesinde ise, web sitelerinin oldukça yetersiz olduğu görülmüştür.
TÜRK KAMU YÖNETİMİNDE MERKEZİ YÖNETİMİN DİYALOJİK İLETİŞİMİ: BAKANLIKLARIN WEB SİTELERİ ÖRNEĞİ
Keywords: Communication and Media Studies; İletişim ve Medya Çalışmaları